Magnetic-Driven Hydrogel Microrobots Selectively Enhance Synthetic Lethality in MTAP-Deleted Osteosarcoma - Mu, Haoran; Liu, Chenlu; Zhang, Qi; Meng, Huanliang; Yu, Shimin; Zeng, Ke; Han, Jing; Jin, Xinmeng; Shi, Shi; Yu, Peiyao; Li, Tianlong; Xu, Jing; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Drugs based on synthetic lethality have advantages such as inhibiting the tumor growth and affecting the normal tissue in vivo. However, specific targets for osteosarcoma have not been acknowledged yet. In this study, a non-targeted but controllable drug delivery system has been applied to selectively enhance synthetic lethality in osteosarcoma in vitro, by using the magnetic-driven hydrogel microrobots. Methods: In this study, EPZ015666, a PRMT5 inhibitor, was selected as the synthetic lethality drug. Then the drug was carried by hydrogel microrobots contained Fe3O4. Morphological characteristics of the microrobots were detected by using the electron microscopy. In vitro drug effect was detected by CCK-8 assay kit, western blotting and etc. Swimming of microrobots was observed by a timing microscope. Selective inhibition was verified by cultured tumors in an increasing magnetic field. Results: Genomic mutation of MTAP deletion occurred commonly in pan-cancer in TCGA database (nearly 10.00%), and in osteosarcoma in TARGET database (23.86%). HOS and its children, 143B and HOS/MNNG, were detected MTAP deletion according to CCLE database and RT-PCR. EPZ015666, the PRMT5 inhibitor, could reduce the SDMA modification and inhibition the tumor growth of 143B and HOS/MNNG. The hydrogel microrobot drug delivery system was synthesized and the drug was stained by rhodamine. The microrobots were powered actively by magnetic field. A stimulation of selected inhibition of microrobots was performed and a lower cell viability of tumor cells was detected by adding a high dose of microrobots. Conclusion: Our magnetic-driven drug delivery system could carry synthetic lethality drugs. Meanwhile, the selective inhibition of this system could be easily controlled by programming the strength of the magnetic field.